A well defect-suitable and high-strength biomimetic squid type II gelatin hydrogel promoted in situ costal cartilage regeneration via dynamic immunomodulation and direct induction manners. (May 2020) - Dai, Meilu; Sui, Baiyan; Hua, Yujie; Zhang, Yiqing; Bao, Bingkun; Lin, Qiuning; Liu, Xin; Zhu, Linyong; Sun, Jiao
Abstract: Reconstructing segmental costal cartilage defects resulting from autologous cartilage grafts in plastic surgery remains a challenge. The present study focused on a biomimetic strategy for in situ costal cartilage regeneration that did not rely on an autogenous/xenogenous tissue graft. A multifunctional biomimetic SGII/HA-DN hydrogel based on a "chemical-curing, shaping, and light-curing" gelation system was developed and evaluated for its mechanical properties, clinical applications and biological functions. This hydrogel showed good suitability to repair defects and a high mechanical support strength (11 MPa, which is close to the natural strength of costal cartilage). Biologically, the hydrogel exhibited dual-immunomodulatory effects on the pro-inflammatory/anti-inflammatory phenotypes of neutrophils and M1/M2 macrophage polarization and subsequently promoted the chondrogenesis of cartilage stem/progenitor cells through both direct induction and indirect stimulation by the M2 macrophage-mediated TGF-β/Smad pathway. Furthermore, this SGII/HA-DN hydrogel could regulate the local microenvironment, inducing new costal cartilage regeneration in vivo . Our findings demonstrate that the newly developed multifunctional SGII/HA-DN hydrogel provides a strategy with high prospect for the biomimetic repair of segmental costal cartilage defects in clinical practice. Graphical abstract: A biomimetic and multifunctional squid type II gelatin/hyaluronic acid double-network hydrogel was developed for the donor-site reconstruction of segmental costal cartilage defects. This hydrogel showed good suitability for defect repair and a high mechanical strength. Moreover, this hydrogel regulated the local microenvironment via the dynamic immunomodulation of neutrophils and macrophages, inducing the chondrogenesis of cartilage stem/progenitor cells and promoting costal cartilage regeneration in vitro and in vivo . Image 1